Mechanical and Morphological Properties of Tropical Wood Polymer Nanocomposite (WPNC) - Mohd Saiful, Islam; Hamdan, S.; Rusop, M.; Rahman, M.R. (Trans Tech Publications, 2013)
A novel route to wood modification by impregnation of nanoclay combined with phenol formaldehyde (PF) resin is developed in this study. Wood polymer nanocomposites (WPNCs) were prepared from several tropical wood species by impregnating the woods with PF/nanoclay formulations. The vacuum-pressure method was used to impregnate the samples with PF/nanoclay prepolymer mixture. The formation of wood polymer nanocomposites and the location of impregnated materials inside wood were confirmed through SEM image and XRD pattern respectively. The PF/nanoclay loading achievable was found to be dependent on the properties of wood species. Low loading was observed for the high density wood species. Mechanical strength of fabricated WPNCs in terms of modulus of elasticity (MOE) was found to be significantly improved. Furthermore, morphological properties of raw wood and WPNC samples were evaluated by scanning electron microscopy (SEM) and XRD analysis and a change in morphological properties was also observed for WPNC.